Formation of a New Urethral Channel in Male Dogs Using Jejunal Segment: An Experimental Study - Gunay, Cihan; Sagliyan, Aydin; Han, Mehmet Cengiz; Yaman, Ihsan (Medwell Online, 2009)
The aim of this study was to determine the usability of a jejunal flap in male dogs to treat cases of serious urethral damage caused by tumor, trauma or innate anomalies that occur in the urethra. Seven adult dogs were used in the study. Following xylazine-ketamine-isoflurane anesthesia, using median laparotomy, we penetrated the abdominal cavity. A 10-15 cm long intestinal segment was formed by enterectomy. One end of this intestinal segment was attached to the prostatic urethra with stitches. The other end was inserted through a hole formed by prepicium mucosa and was fixed to that area. Subsequent observation over a period of 4 months showed that the animals were able to urinate without discomfort and no stoma and stenosis developed in anastomosis area. Histopathologic examinations indicated that urethral jejenum perfectly adapted to the area and the structure of intestinal mucosa changed in time. As a result of the study, it was concluded that jejunal flap is suitable for urethral reconstruction.
Keywords: Urethra; jejunal flap; dog; experimental study; synthetic materials; abdominal cavity